Teori Kites dalam Pola Asuh Anak - Ahmad Suradi (Muróbbî: Jurnal Ilmu Pendidikan, 2018)
Child care pattern must be done with good education, if done wrongly, it will have an impact that is not good for the development of soul and body, and of course also will impact on the surrounding environment. This can be seen from some phenomenon that recently rampant happened. Child care pattern should be done with a good education, if done wrongly, it will have an impact that is not good for the development of the soul and body, and of course also will have an impact on the surrounding environment. Regarding self-preservation, Islam has actually given a warning to humans. The role that humans must perform consists of two paths, namely the horizontal path and the second vertical path. When viewed from various forms of parenting, in essence almost the same. For example autopsy, over protection, over discipline. Domination, favoritism, parental and authoritarian ambition, all emphasize excessive attitudes of power, discipline and obedience.